Motivation Factor That Affect Job Performance: A Case of Food and Beverage Technology Business in Entrepreneurship Student Class of 2020 School of Business and Management Institut Teknologi Bandung and Its Affect to Moringa Culinary Company (Journal of Innovation, Business and Entrepreneurship, 2020)
The increasing number of entrepreneurs in Indonesia is quite rapid, the government is exerting its efforts to increase the number with several strategies, one of which is making connections to universities in Indonesia, one of which is the School of Business and Management of the Bandung Institute of Technology, there are entrepreneurship study programs in it that require students to have business from college, one of the business fields is food and beverage technology based business. In this study the authors wanted to find out whether the motivational factors of students in running a food and beverage technology business. by using the theory of Student Motivation in Doing Business from Siswadi on 2014 which categorizes the factors that influence students' motivation in doing business from internal, external and education and learning factors. and to find out the factors that influence these authors use data collection using qualitative data methods by conducting pilot tests, interviews and focus group discussions in his research. Data analysis was analyzed through content analysis. The results of this analysis are external factors which are the strongest factors in the influence of students in running a business, for internal factors, education and learning factors.Keywords: Food and Beverage Business, Motivation Student in doing Business,  Motivation Factor